Study Of Mechanism Of Injury, Pattern Of Injury And Mode Of Transport Influencing Outcome Of Trauma Patients At Level I Trauma Center: A Retrospective And Prospective Observational Study - Tripathi, Shiv Shanker; Kumar Srivastava, Utkarsh; Verma, Pankaj; Ratan Singh Yadav, Rajeev (Journal of Neonatal Surgery, 2025)
Approximately 1.19 million people die each year as a result of road traffic crashes. Road traffic injuries are the leading cause of death for children and young adults aged 5–29 years. 92%t of the world's fatalities on the roads occur in low- and middle-income countries, even though these countries have around 60% of the world's vehicles.In this we understand major mechanism of injury and to correlate with anatomical injury and to study pattern of injuries and their outcome. This retrospective prospective observational study was done in department of Emergency Medicine in of Dr. Ram Manohar Lohia Institute of Medical Sciences, Lucknow. It was carried out for 18 months. All trauma patients attending surgical causality, department of trauma surgery, orthopedic, male and female both were included.Patient leaves against medical advice, absconded patient, referred to another center were excluded.150 retrospective and 150 prospectivepatients taken in this study.Male were more common in our study. Only 33.63% patients were used safety device. Two wheelers and drivers were more affected in RTA. In our study maximum patients were reach our hospital after 24 hours and mode of transportation was use Government Ambulance or private vehicle. Most of the patients given first add in Government Hospital/Clinic by paramedical staff or doctor and referred from government hospital. Head was the most injured part observed in our study. Most of the patients were admitted and thereafter discharged from our hospital. We observed no differences in hospital complications between patients. Further investigation is warranted to identify the underlying causes of complications to facilitate reduction and improve patient outcomes. Increasing awareness of the EMS contact number may increase EMS utilization. Finally, effective preventive programs to prevent MVC are desperately needed reduce associated complications and improve population health. IED: Improvised Explosive Devices, ATLS: Advanced Trauma Life Support, CO: Cardiac Output, SNS:Sympathetic Nervous System, SVR: Systemic Vascular Resistance, BAC: Blood Alcohol Concentration, GSW: Gunshot Wounds, LOS: Length of Stay, TCD: Transcranial Doppler